2014
DOI: 10.1007/s00253-014-5789-1
|View full text |Cite
|
Sign up to set email alerts
|

MET2 affects production of hydrogen sulfide during wine fermentation

Abstract: The production of hydrogen sulfide (H2S) during yeast fermentation contributes negatively to wine aroma. We have mapped naturally occurring mutations in commercial wine strains that affect production of H2S. A dominant R310G mutant allele of MET2, which encodes homoserine O-acetyltransferase, is present in several wine yeast strains as well as in the main lab strain S288c. Reciprocal hemizygosity and allele swap experiments demonstrated that the MET2 R310G allele confers reduced H2S production. Mutations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…Previously, Lage et al [22] have observed the same effect using a co-culture of H. guilliermondii and the same commercial strain of S. cerevisiae used herein. Later, Barbosa et al [79] showed that the presence of the non-Saccharomyces strain of H. guilliermondii had an evident regulatory control of S. cerevisiae genes that impact H 2 S liberation during wine fermentation [86][87][88]. In this line, we could only speculate that Mp39 could have a similar effect on the transcriptome of S. cerevisiae.…”
Section: S Cerevisiae and M Pulcherrima Single And Mixed Fermentationsmentioning
confidence: 85%
“…Previously, Lage et al [22] have observed the same effect using a co-culture of H. guilliermondii and the same commercial strain of S. cerevisiae used herein. Later, Barbosa et al [79] showed that the presence of the non-Saccharomyces strain of H. guilliermondii had an evident regulatory control of S. cerevisiae genes that impact H 2 S liberation during wine fermentation [86][87][88]. In this line, we could only speculate that Mp39 could have a similar effect on the transcriptome of S. cerevisiae.…”
Section: S Cerevisiae and M Pulcherrima Single And Mixed Fermentationsmentioning
confidence: 85%
“…M2 was selected as the genetic background for the transcriptomic study and for the F 1 hybrids because it is homozygous at all of the ten microsatellite loci tested and a good fermenter at low temperatures. The microsatellite genotype of M2 is identical to AWRI796, Oenoferm Tipico, Lalvin W15, and Anchor WE372 (Gardner et al 2006) and the full genome sequence is available for M2 (Huang et al 2014), AWRI796 (Borneman et al 2011) and WE372 (Cromie et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the 52 genomes sequenced here, a further 72 S. cerevisiae and 37 S. paradoxus genomes were obtained from the Saccharomyces Genome Database (http://yeastgenome.org), NCBI, the Saccharomyces Genome Resequencing Project (https://sanger.ac.uk/research/projects/genomeinformatics/sgrp.html) and from Huang, Roncoroni and Gardner (2014) in the form of consensus genomes and/or raw data. To obtain an accurate estimation of the relatedness of the genomes, we extracted the well-known set of 106 orthologous loci spread through the genome of S. cerevisiae and present in all Saccharomyces species (Rokas et al .…”
Section: Methodsmentioning
confidence: 99%